Analysis of technological features of using assembly machines and mechanisms in the construction of large-span buildings - RASHKIVSKYI, Volodymyr; IGNATENKO, Oleksandr (Ways to Improve Construction Efficiency, 2025)
This article presents an analysis of the technological features of the use of assembly machines and mechanisms in the construction of large-span buildings over the past seventy years. The technical characteristics of modern machines and mechanisms involved in the processes of lifting ultra-heavy and oversized structures have also been analyzed. According to the principles of organizational and technological structuring and the classification of assembly methods, mobile and limited-mobility cranes are involved in the processes of pre-lifting enlargement of roofing structures on assembly stands, followed by the lifting of large-span roof blocks to their design elevation marks. Pre-lifting assembly and lifting of roofing blocks to the level of the column heads of the frame are carried out using cranes by the method of free lifting with pulling. Non-mobile installation mechanisms are involved exclusively in technological processes for moving assembled roofing blocks from the level of the assembly stands to the design height by methods of forced lifting (moving) through pulling or pushing. In the present circumstances, during the construction of new or the reconstruction of war-damaged large-span reinforced concrete and metal structures in densely built-up areas, the movement of mobile and limited-mobility cranes along the external perimeter of construction sites is restricted and often impossible. Mobile cranes can only move within the internal space of the building under construction, between the columns of the supporting framework, and can be used in the processes of pre-lifting assembly of large-span roof structures. The movement of fully assembled structural and technological blocks of roof coverings from the level of the assembly stands to the level of the column heads in densely built-up areas can be carried out by non-mobile assembly mechanisms, which use the supporting columns as vertical guides and bearing surfaces in the technological processes of roof construction.